Management of dysphagia following radiation therapy and tracheostomy - Jagtap, Mansi A.; Shrivastava, Shlok (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Dysphagia (swallowing disorders) have been reported commonly following oral and laryngeal cancers. Patients undergoing radiation therapy usually complaint of deterioration in swallowing functions due to fibrosis. Also, presence of tracheostomy causes aspiration while swallowing by reducing the hyolaryngeal excursion and also leading to inadequate subglottic pressure and fixation of trachea. An 85 year old male with history of supraglottic carcinoma managed by radiation therapy and tracheostomy reported for swallowing assessment. Detailed assessment was performed using clinical swallow examination and instrumental assessment (modified barium swallow) using thin, thick and paste consistencies. Results revealed no overt signs of penetration on clinical swallow while modified barium swallow revealed severe intraswallow aspiration due to incomplete hyolaryngeal elevation on all consistencies (more for liquids). This clearly indicated silent aspiration. Swallowing therapy focused on hyolaryngeal elevation using protective maneuvers. Reassessment was performed following 7 sessions using the above mentioned protocol which revealed improvement in hyolaryngeal elevation (complete hyolaryngeal closure during swallow) and no aspiration on all consistencies. Dysphagia is a common complication following radiation therapy. An instrumental assessment is mandatory to rule out silent aspirations as seen in the present case. Swallowing intervention has an important role to treat dysphagia following radiation therapy and has shown to be effective in the present study and literature. Hence, patients who have indications for radiation therapy should undergo swallowing intervention in order to ensure safe oral intake.